An IoT-Based Framework for Smart Water Supply Systems Management - Rosiberto Gonçalves; Jesse J. M. Soares; Ricardo M. F. Lima (Future Internet, 2020)
The world’s population growth and climate changes increase the demand for high-quality water. This fact forces humankind to create new water management strategies. Smart cities have successfully applied the Internet of Things (IoT) technology in many sectors. Moreover, Complex Event Processing (CEP) can analyze and process large data sets produced by IoT sensors in real-time. Traditional business processes are too rigid in expressing the dynamic behavior of water supply systems. Every execution path must be explicitly specified. On the other hand, declarative business processes allow execution paths that are not prohibited by the rules, providing more flexibility for water supply managers. This paper joins together IoT, CEP, and declarative processes to create a powerful, efficient, and flexible architecture (REFlex Water) to manage water supply systems. To the knowledge of the authors, REFlex Water is the first solution to combine these technologies in the context of water supply systems. The paper describes the REFlex Water architecture and demonstrates its application to a real water system from a Brazilian municipality. Results are promising, and the managers from the Brazilian water company are expanding the use of REFlex Water to other sectors of their water supply system.